2019
DOI: 10.1111/gbb.12576
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal amygdalae and hippocampi are influenced by genotype and prenatal environment, and reflected in the neonatal DNA methylome

Abstract: The amygdala and hippocampus undergo rapid development in early life. The relative contribution of genetic and environmental factors to the establishment of their developmental trajectories has yet to be examined. We performed imaging on neonates and examined how the observed variation in volume and microstructure of the amygdala and hippocampus varied by genotype, and compared with prenatal maternal mental health and socioeconomic status. Gene × Environment models outcompeted models containing genotype or env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 103 publications
(165 reference statements)
0
13
0
Order By: Relevance
“…Genetic influence also deserves consideration. One study that explored genome-wide SNP’s (single nucleotide polymorphisms) interactions with prenatal environments indicated that gene-environment interdependence best explains variation in amygdalar and hippocampal measures: right amygdalar volume in interaction with prenatal maternal depression, and hippocampal white matter asymmetry with prenatal maternal anxiety and household income ( Ong et al, 2019 ). In an Asian population, maternal depressive symptoms were connected with larger right amygdalar volumes among newborns having a high genetic risk profile for depression, whereas, in contrast, the same positive connection was observed in a low risk group in an American population.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic influence also deserves consideration. One study that explored genome-wide SNP’s (single nucleotide polymorphisms) interactions with prenatal environments indicated that gene-environment interdependence best explains variation in amygdalar and hippocampal measures: right amygdalar volume in interaction with prenatal maternal depression, and hippocampal white matter asymmetry with prenatal maternal anxiety and household income ( Ong et al, 2019 ). In an Asian population, maternal depressive symptoms were connected with larger right amygdalar volumes among newborns having a high genetic risk profile for depression, whereas, in contrast, the same positive connection was observed in a low risk group in an American population.…”
Section: Discussionmentioning
confidence: 99%
“…Sample sizes and ages at scan are shown in Supplementary Table 1 . Fifty-two studies were completely cross-sectional and performed only one scan per each subject ( Hazlett et al, 2012 ; Deniz Can et al, 2013 ; Deoni et al, 2013 , 2015 ; Gao et al, 2013 ; O’Muircheartaigh et al, 2013 , 2014 ; Qiu et al, 2013a , 2015b ; Broekman et al, 2014 ; Dean et al, 2014b , c , 2017 , 2018a , b ; Grewen et al, 2014 ; Travis et al, 2014 ; Zhang et al, 2014 ; Donald et al, 2015 ; Langer et al, 2015 ; Ou et al, 2015 ; Poh et al, 2015 ; Spann et al, 2015a , b , 2020a , b ; Ferradal et al, 2016 , 2019 ; Li et al, 2016 ; Sethna et al, 2016 ; Adibpour et al, 2018 , 2020 ; Lugo-Candelas et al, 2018 ; Monnelly et al, 2018 ; Chen et al, 2019 ; Hernandez-Castillo et al, 2019 ; Lebenberg et al, 2019 ; Lehtola et al, 2019 ; Ong et al, 2019 ; Tuulari et al, 2019 ; Acosta et al, 2020a , b , 2021 ; Alexander et al, 2020 ; Bruchhage et al, 2020 ; Camacho et al, 2020 ; Dowe et al, 2020 ; Fenchel et al, 2020 ; Gale-Grant et al, 2020 ; Graham et al, 2020 ; Merhar et al, 2020 ; Merz et al, 2020 ). The remaining studies ( n = 34) were longitudinal and conducted serial scans on the same individuals ( Geng et al, 2012 , 2016 ; ...…”
Section: Resultsmentioning
confidence: 99%
“…A number of different approaches to wrapping the infants were provided, varying from only wrapping them in sheets to placing them into an immobilizer. Several studies ( n = 23) used specific vacuum immobilization mats, bags, or pillows to stabilize the child and reduce natural movement from breathing ( Deoni et al, 2013 ; Zhang et al, 2014 ; Ou et al, 2015 ; Croteau-Chonka et al, 2016 ; Li et al, 2016 ; Dean et al, 2014a , b , c , 2015b , 2017 , 2018a , b ; Dai et al, 2019a , b ; Hernandez-Castillo et al, 2019 ; Lehtola et al, 2019 ; Ong et al, 2019 ; Tuulari et al, 2019 ; Camacho et al, 2020 ; Dowe et al, 2020 ; Graham et al, 2020 ; Merhar et al, 2020 ; Remer et al, 2020 ). Dean et al (2014a) reported placing a mat under the child before the child fell asleep and once asleep the immobilizer was wrapped around the child.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence from human 34 and animal studies 35 that epigenetic change in non-imprinted genes may be relevant to the link between early life adversity and hippocampal development but the evidence for imprinted genes has so far been indirect or inferred. Offspring methylation within the imprinted gene MEST has been linked to exposure to maternal stress 36 , which has in turn been linked to www.nature.com/scientificreports/ hippocampal volumes, and there is some genetic evidence that the imprinted gene L3MBTL may work with a subnetwork of genes to influence hippocampal volume, microstructure and asymmetry 37 . White matter hyperintensities in the brain are the consequence of cerebral small vessel disease and are important risk factors for cognitive and functional impairment dementia, stroke, worse outcomes after stroke, gait instability, late-life depression, and death 23,38,39 .…”
Section: Discussionmentioning
confidence: 99%